Thermal-insulation anti-cracking dry-mixed mortar and preparation method thereof
Through scientific proportioning and modification treatment, dry powder mortar containing modified SiO2 aerogel and modified asphalt was prepared, which solved the problem of prone to cracking of traditional dry powder mortar and significantly improved its insulation performance and crack resistance.
Patent Information
- Application Number
- CN202411380494.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-18
AI Technical Summary
Traditional dry powder mortar is prone to cracking during use, which affects its insulation effect and building safety.
The preparation of modified SiO2 aerogel and modified asphalt is adopted using the ratios including silicate cement, expanded perlite, vitrified microbeads, modified SiO2 aerogel, modified asphalt, polypropylene fiber and water retention agent. and add to improve the insulation and crack resistance of the mortar.
It significantly improves the thermal insulation and crack resistance of dry powder mortar, ensures that the mortar forms a solid and dense structure after hardening, reduces heat transfer, and improves toughness and compressive strength.
Smart Images

Figure BDA0005069777020000131 
Figure BDA0005069777020000141 
Figure BDA0005069777020000142
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to heat-insulating and crack-resistant dry-mix mortar and a preparation method thereof. Background Art
[0002] Dry mortar is a premixed building material, which is physically mixed with dry and sieved aggregates (such as quartz sand), inorganic cementitious materials (such as cement) and additives (such as polymers) in a certain proportion. It is transported to the construction site in bags or bulk and can be used directly after adding water and mixing. Dry mortar is widely used in the construction industry to play the role of bonding, lining, protection and decoration in thin layers.
[0003] With the intensification of the global energy crisis and the improvement of environmental awareness, building energy conservation has become the focus of global attention. Building energy conservation is an important way to ease energy pressure, reduce environmental pollution and achieve sustainable development. According to statistics, building energy consumption accounts for nearly 40% of the world's total energy consumption, and with the acceleration of urbanization and the improvement of people's living standards, this proportion is on the rise. Therefore, improving building energy efficiency and reducing building energy consumption have become a global consensus. As an important part of the building's external envelope structure, the thermal insulation performance of the wall directly affects the overall energy consumption of the building. Therefore, the development of efficient and environmentally friendly wall insulation materials and technologies is of great significance to promoting building energy conservation. Traditional on-site mortar has problems such as low efficiency, unstable quality, and serious environmental pollution, which can no longer meet the development needs of the modern construction industry. Dry mortar, as a premixed building material, has the advantages of convenient construction, controllable quality, environmental protection and energy saving. Although traditional dry mortar has a certain thermal insulation effect, it has problems such as easy cracking and poor weather resistance. Especially in the exterior wall insulation system, due to factors such as temperature difference and wind pressure, the insulation layer is prone to fall off and crack, affecting the insulation effect and building safety. Therefore, the development of dry-mixed mortar with excellent insulation effect and crack resistance has become an important research direction in the field of building insulation. Summary of the invention
[0004] The purpose of the present invention is to provide a thermal insulation and crack-resistant dry-mix mortar and a preparation method thereof, so as to solve the technical problem of cracking that is easily occurred in the dry-mix thermal insulation mortar during use in the prior art.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The heat-insulating and crack-resistant dry-mix mortar comprises the following raw materials in parts by weight: 25-40 parts of silicate cement, 15-25 parts of expanded perlite, 10-20 parts of vitrified microspheres, 2-10 parts of modified asphalt, 1-8 parts of modified SiO2 aerogel, 0.5-1 part of polypropylene fiber and 0.2-0.5 parts of water-retaining agent; the modified SiO2 aerogel is prepared from silicon-rich slag as raw material by raw material pretreatment, mixing heating, separation and purification, sol, aging reaction, modification reaction and drying; the modified asphalt is prepared from base asphalt and rubber powder as raw materials by raw material mixing and high-speed shear mixing.
[0007] The water retaining agent is one or both of cellulose ether and starch ether.
[0008] The preparation of modified SiO2 aerogel includes the following steps:
[0009] (1) Raw material pretreatment: the silicon-rich slag is placed in a constant temperature drying oven for drying to obtain dry silicon-rich slag, the dry silicon-rich slag is placed in a jaw crusher for crushing, and after crushing, it is sieved to obtain high-reactivity silicon-rich slag;
[0010] (2) Mixing and heating: Highly reactive silicon-rich slag and sodium hydroxide solution are mixed evenly, and then placed in a reactor for heating, with continuous stirring during the heating period. After the heating is completed, a solid-liquid mixture is obtained;
[0011] (3) separation and purification: centrifuging the solid-liquid mixture, discarding the precipitate after centrifugation, and collecting the supernatant to obtain a sodium silicate solution;
[0012] (4) Sol: Deionized water is added to the sodium silicate solution to dilute it, and ion exchange is performed through a strong acid cation exchange resin to obtain an ion exchange strong acid solution. Ammonia water is then added to the ion exchange strong acid solution to adjust the pH of the solution to obtain a SiO2 sol gel solution.
[0013] (5) Aging reaction: The SiO2 sol-gel solution is placed on an electromagnetic heating stirrer for heating and stirring, and then allowed to stand to obtain a SiO2 hydrogel. An ethanol solution is added to the SiO2 hydrogel to immerse the SiO2 hydrogel, and the solution is placed in a water bath for constant temperature heating, and the ethanol solution is replaced to obtain a SiO2 aged gel.
[0014] (6) Modification reaction: adding a modifier to cyclohexane to obtain a modified solution, adding the modified solution to the aged SiO2 gel to obtain a modified gel solution, placing the modified gel solution in a water bath, and replacing the modified solution until the hydrogel floats on the liquid surface to obtain a modified SiO2 hydrogel;
[0015] (7) Drying: The modified SiO2 hydrogel is rinsed with cyclohexane and then dried in a constant temperature drying oven. After drying, it is naturally cooled to room temperature to obtain a modified SiO2 aerogel.
[0016] Furthermore, in step (1), the temperature of the constant temperature drying oven is 100-110° C., the drying time is 12-16 hours, the jaw crusher is a European PEW series, the feed particle size is 480-1040 mm, and the mesh size of the screen is 100-200 meshes; in step (2), the highly reactive silicon-rich slag is added to the sodium hydroxide solution, the liquid-to-solid ratio is 2-5:1, the concentration of the sodium hydroxide solution is 10-25wt%, the reaction temperature is 90-150° C., and the reaction time is 1-10 hours; in step (3), the centrifugal speed is 4000-6000 r / min, and the centrifugal time is 10-15 min; in step (4), the volume ratio of the sodium silicate solution to deionized water is 1:3-6, the solution pH is adjusted to 2 after the strong acid cation exchange resin, and ammonia water is added to adjust the solution pH to 7-9; in step (5), the electrochemical reaction is carried out. The temperature of the magnetic heating stirrer is set to 40°C, the speed is set to 30-100 rpm, and the mixture is allowed to stand for 6-48 hours. The concentration of the ethanol solution is 95-99vt%, the temperature of the water bath is 40°C, and the ethanol solution is replaced every 8 hours for 3 times. In step (6), the modifier is a mixture of dimethyldichlorosilane and tetramethyldisiloxane, dimethyldichlorosilane and tetramethyldisiloxane are mixed in equal amounts, the volume ratio of cyclohexane to the modifier is 1:1, the modified solution accounts for 10-30% of the volume of the SiO2 aged gel, the temperature of the water bath is 40°C, the modified solution is replaced every 12 hours, for a total of 2 times, for a duration of 24 hours. In step (7), step drying is performed, first at 60-70°C for 4-6 hours, then at 120-130°C for 4-6 hours, and the heating rate is set to 3°C / min.
[0017] The preparation of modified asphalt includes the following steps:
[0018] S1. Mixing raw materials: After heating the base asphalt, slowly add the rubber powder into the base asphalt and stir evenly to obtain asphalt rubber powder adhesive;
[0019] S2. High-speed shear mixing: Use a high-speed shearing machine to strongly shear the asphalt rubber powder adhesive and continuously stir it to obtain modified asphalt.
[0020] Furthermore, the base asphalt in S1 is 70# base asphalt, the heating temperature is 170-180°C, the rubber powder is one or two of styrene-butadiene rubber powder and waste tire rubber powder, and the rubber powder accounts for 10-30% of the asphalt mass; the shear temperature in S2 is 180-190°C, and the stirring time is 20-30 minutes.
[0021] The present invention also provides a method for preparing a heat-insulating and crack-resistant dry-mix mortar, comprising the following steps:
[0022] M1. Premixing: Mix expanded perlite and vitrified microspheres to obtain mixed aggregate, then add silicate cement to the mixed aggregate, preliminarily stir evenly to obtain a premix;
[0023] M2. Remixing: adding the modified SiO2 aerogel and the modified asphalt into the premix, stirring evenly to obtain a modified premix;
[0024] M3. Post-mixing: Add polypropylene fiber and water-retaining agent into the modified premix, stir thoroughly to obtain heat-insulating and crack-resistant dry-mix mortar.
[0025] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0026] 1. The present invention prepares heat-insulating and crack-resistant dry-mixed mortar by scientifically proportioning silicate cement, expanded perlite, vitrified microspheres, modified SiO2 aerogel, modified asphalt, polypropylene fiber and water-retaining agent. As lightweight porous aggregates, expanded perlite and vitrified microspheres have the characteristics of low thermal conductivity and high porosity, which can effectively reduce the transfer of heat and significantly improve the thermal insulation performance of mortar. As an advanced nano-insulation material, modified SiO2 aerogel can further enhance the thermal insulation effect of mortar. As a fiber-reinforced material, polypropylene fiber significantly improves the toughness and crack resistance of mortar, effectively resists the generation and development of cracks caused by external forces, and the addition of modified asphalt can improve the bonding force and cohesion of mortar, so that mortar forms a more solid and dense structure after hardening, thereby enhancing the crack resistance of mortar. In addition, the heat-insulating and crack-resistant dry-mixed mortar of the present invention exists in the form of dry powder, which is convenient for storage, transportation and construction. It can be used by adding an appropriate amount of water and stirring evenly at the construction site, which greatly simplifies the construction process.
[0027] 2. The present invention optimizes the pore structure of SiO2 aerogel by modifying it, and enhances its thermal stability. During the modification process, the addition of dimethyldichlorosilane and tetramethyldisiloxane improves the surface properties of SiO2 aerogel, making it more evenly dispersed in dry-mixed mortar, and improving its compatibility and bonding with the matrix material. In addition, the modified SiO2 aerogel has an ultra-low density and high porosity, so the thermal conductivity is lower and the pore structure is more stable, which significantly improves the thermal insulation performance of the dry-mixed mortar.
[0028] 3. The modified asphalt prepared by mixing rubber powder with base asphalt and subjecting it to high-speed shearing has better flexibility and crack resistance. The addition of rubber powder significantly improves the elasticity and low-temperature crack resistance of asphalt. This is because rubber particles can form a network structure in the asphalt matrix, absorb and disperse stress, and thus effectively resist deformation and cracking caused by temperature changes. In addition, the use of modified asphalt also improves the bonding force and construction performance of dry mortar, ensuring the stability and durability of the mortar under different environmental conditions. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Embodiment 1:
[0031] The present embodiment provides a heat-insulating and crack-resistant dry-mix mortar, comprising the following raw materials in parts by weight: 40 kg of silicate cement, 15 kg of expanded perlite, 10 kg of vitrified microspheres, 1 kg of modified SiO2 aerogel, 2 kg of modified asphalt, 0.5 kg of polypropylene fiber and 0.2 kg of a water-retaining agent; the water-retaining agent is cellulose ether.
[0032] Specifically, the preparation of modified SiO2 aerogel includes the following steps:
[0033] (1) Raw material pretreatment: The silicon-rich slag is placed in a constant temperature drying oven for drying at a temperature of 100° C. for 16 hours to obtain dry silicon-rich slag, and the dried silicon-rich slag is placed in a jaw crusher for crushing. After crushing, the dried silicon-rich slag is sieved through a 100-mesh sieve to obtain high-reactivity silicon-rich slag;
[0034] (2) Mixing and heating: 1000 g of highly reactive silicon-rich slag was mixed with 2 L of 10 wt% sodium hydroxide solution, and then placed in a reactor for heating at 90° C. The mixture was stirred continuously during heating and the reaction time was 10 hours to obtain a solid-liquid mixture;
[0035] (3) separation and purification: centrifuging the solid-liquid mixture at a centrifugal speed of 4000 r / min for 10 min. After the centrifugation, discarding the precipitate and collecting the supernatant to obtain a sodium silicate solution;
[0036] (4) Sol: Take 200 mL of sodium silicate solution, add 600 mL of deionized water to dilute it, and perform ion exchange through a strong acid cation exchange resin to make the solution pH = 2 to obtain an ion exchange strong acid solution, then add ammonia water to the ion exchange strong acid solution to adjust the solution pH = 7 to obtain a SiO2 sol gel solution.
[0037] (5) Aging reaction: 100 mL of SiO2 sol-gel solution was placed on an electromagnetic heating stirrer for heating and stirring at 40°C and 30 rpm, and then allowed to stand for 48 hours to obtain SiO2 hydrogel. A 95% ethanol solution was added to the SiO2 hydrogel to immerse the SiO2 hydrogel, and the solution was placed in a water bath for constant temperature heating at 40°C. The ethanol solution was replaced every 8 hours, and the solution was replaced three times to obtain SiO2 aged gel.
[0038] (6) Modification reaction: 2.5 mL of dimethyldichlorosilane and 2.5 mL of tetramethyldisiloxane were added to 5 mL of cyclohexane to obtain a modified solution, 100 mL of SiO2 aged gel was added to the modified solution to obtain a modified gel solution, and the modified gel solution was placed in a water bath at a temperature of 40°C. The modified solution was replaced every 12 hours for a total of 2 times until the hydrogel floated on the liquid surface to obtain a modified SiO2 hydrogel;
[0039] (7) Drying: The modified SiO2 hydrogel was rinsed with cyclohexane and then dried in a constant temperature drying oven. The drying was carried out by step drying, first at 60°C for 6 hours and then at 120°C for 6 hours. The heating rate was set at 3°C / min. After drying, it was naturally cooled to room temperature to obtain the modified SiO2 aerogel.
[0040] Specifically, the preparation of modified asphalt includes the following steps:
[0041] S1. Mixing raw materials: After heating 1000g of 70# base asphalt to 180°C, slowly add 100g of styrene-butadiene rubber powder into the base asphalt and stir evenly to obtain asphalt rubber powder adhesive;
[0042] S2. High-speed shear mixing: Use a high-speed shearing machine to strongly shear the asphalt rubber powder adhesive at a shearing temperature of 180°C and stir continuously for 30 minutes to obtain modified asphalt.
[0043] This embodiment also provides a method for preparing heat-insulating and crack-resistant dry-mix mortar, comprising the following steps:
[0044] M1. Premixing: 15 kg of expanded perlite and 10 kg of vitrified microspheres are mixed to obtain a mixed aggregate, and then 40 kg of Portland cement is added to the mixed aggregate, and preliminarily stirred to obtain a premix;
[0045] M2, remixing: adding 5 kg of modified SiO2 aerogel and 2 kg of modified asphalt into the premix, stirring evenly to obtain a modified premix;
[0046] M3. Post-mixing: Add 0.5 kg of polypropylene fiber and 0.2 kg of cellulose ether into the modified premix, stir thoroughly to obtain a heat-insulating and crack-resistant dry-mix mortar.
[0047] Embodiment 2:
[0048] The present embodiment provides a heat-insulating and crack-resistant dry-mix mortar, comprising the following raw materials in parts by weight: 30 kg of silicate cement, 20 kg of expanded perlite, 15 kg of vitrified microspheres, 3 kg of modified SiO2 aerogel, 4 kg of modified asphalt, 0.7 kg of polypropylene fiber and 0.3 kg of a water-retaining agent; the water-retaining agent is cellulose ether.
[0049] Specifically, the preparation of modified SiO2 aerogel includes the following steps:
[0050] (1) Raw material pretreatment: The silicon-rich slag is placed in a constant temperature drying oven and dried at a temperature of 102° C. for 15 hours to obtain dry silicon-rich slag, and the dried silicon-rich slag is placed in a jaw crusher for crushing, and after crushing, it is sieved through a 120-mesh screen to obtain high-reactivity silicon-rich slag;
[0051] (2) Mixing and heating: 1000 g of highly reactive silicon-rich slag was mixed evenly with 3 L of 15 wt% sodium hydroxide solution, and then placed in a reactor for heating at a reaction temperature of 110° C. The mixture was stirred continuously during heating and the reaction time was 8 hours to obtain a solid-liquid mixture;
[0052] (3) separation and purification: centrifuging the solid-liquid mixture at a centrifugal speed of 4500 r / min for 15 min. After the centrifugation, discarding the precipitate and collecting the supernatant to obtain a sodium silicate solution;
[0053] (4) Sol: Take 200 mL of sodium silicate solution, add 800 mL of deionized water to dilute it, and perform ion exchange through a strong acid cation exchange resin to adjust the solution pH to 2 to obtain an ion exchange strong acid solution. Then, add ammonia water to the ion exchange strong acid solution to adjust the solution pH to 7.5 to obtain a SiO2 sol gel solution.
[0054] (5) Aging reaction: 100 mL of SiO2 sol-gel solution was placed on an electromagnetic heating stirrer for heating and stirring at 40°C and 50 rpm, and then allowed to stand for 10 hours to obtain SiO2 hydrogel. 96vt% ethanol solution was added to the SiO2 hydrogel to immerse the SiO2 hydrogel, and then placed in a water bath for constant temperature heating at 40°C. The ethanol solution was replaced every 8 hours, and replaced three times to obtain SiO2 aged gel.
[0055] (6) Modification reaction: 3 mL of dimethyldichlorosilane and 3 mL of tetramethyldisiloxane were added to 6 mL of cyclohexane to obtain a modified solution, 100 mL of SiO2 aged gel was added to the modified solution to obtain a modified gel solution, and the modified gel solution was placed in a water bath at a temperature of 40°C. The modified solution was replaced every 12 hours for a total of 2 times until the hydrogel floated on the liquid surface to obtain a modified SiO2 hydrogel;
[0056] (7) Drying: The modified SiO2 hydrogel was rinsed with cyclohexane and then dried in a constant temperature drying oven. The drying was carried out by step drying, first at 65°C for 5 hours and then at 125°C for 5 hours. The heating rate was set to 3°C / min. After drying, it was naturally cooled to room temperature to obtain the modified SiO2 aerogel.
[0057] Specifically, the preparation of modified asphalt includes the following steps:
[0058] S1. Mixing raw materials: After heating 1000g of 70# base asphalt to 175°C, slowly add 200g of styrene-butadiene rubber powder into the base asphalt and stir evenly to obtain asphalt rubber powder adhesive;
[0059] S2. High-speed shear mixing: Use a high-speed shearing machine to strongly shear the asphalt rubber powder adhesive at a shearing temperature of 185°C and stir continuously for 25 minutes to obtain modified asphalt.
[0060] This embodiment also provides a method for preparing heat-insulating and crack-resistant dry-mix mortar, comprising the following steps:
[0061] M1. Premixing: Mix 20 kg of expanded perlite and 15 kg of vitrified microspheres to obtain a mixed aggregate, then add 30 kg of Portland cement to the mixed aggregate, and stir preliminarily to obtain a premix;
[0062] M2, remixing: adding 10 kg of modified SiO2 aerogel and 4 kg of modified asphalt into the premix, stirring evenly to obtain a modified premix;
[0063] M3. Post-mixing: Add 0.7 kg of polypropylene fiber and 0.3 kg of cellulose ether into the modified premix, stir thoroughly to obtain a heat-insulating and crack-resistant dry-mix mortar.
[0064] Embodiment 3:
[0065] The present embodiment provides a heat-insulating and crack-resistant dry-mix mortar, comprising the following raw materials in parts by weight: 30 kg of silicate cement, 20 kg of expanded perlite, 15 kg of vitrified microspheres, 6 kg of modified SiO2 aerogel, 6 kg of modified asphalt, 0.8 kg of polypropylene fiber and 0.4 kg of a water-retaining agent; the water-retaining agent is starch ether.
[0066] Specifically, the preparation of modified SiO2 aerogel includes the following steps:
[0067] (1) Raw material pretreatment: The silicon-rich slag is placed in a constant temperature drying oven and dried at a temperature of 110° C. for 14 hours to obtain dry silicon-rich slag, and the dried silicon-rich slag is placed in a jaw crusher for crushing, and after crushing, it is sieved through a 200-mesh screen to obtain high-reactivity silicon-rich slag;
[0068] (2) Mixing and heating: 1000 g of highly reactive silicon-rich slag was mixed evenly with 5 L of 25 wt% sodium hydroxide solution, and then placed in a reactor for heating at a temperature of 150° C. The mixture was stirred continuously during heating and the reaction time was 10 hours to obtain a solid-liquid mixture;
[0069] (3) separation and purification: centrifuging the solid-liquid mixture at a centrifugal speed of 6000 r / min for 10 min. After the centrifugation, discarding the precipitate and collecting the supernatant to obtain a sodium silicate solution;
[0070] (4) Sol: Take 200 mL of sodium silicate solution, add 1200 mL of deionized water to dilute it, and perform ion exchange through a strong acid cation exchange resin to adjust the solution pH to 2 to obtain an ion exchange strong acid solution. Then, add ammonia water to the ion exchange strong acid solution to adjust the solution pH to 9 to obtain a SiO2 sol gel solution.
[0071] (5) Aging reaction: 100 mL of SiO2 sol-gel solution was placed on an electromagnetic heating stirrer for heating and stirring at 40°C and 80 rpm, and then allowed to stand for 40 hours to obtain SiO2 hydrogel. 99vt% ethanol solution was added to the SiO2 hydrogel to immerse the SiO2 hydrogel, and the solution was placed in a water bath for constant temperature heating at 40°C. The ethanol solution was replaced every 8 hours, and replaced three times to obtain SiO2 aged gel.
[0072] (6) Modification reaction: 6 mL of dimethyldichlorosilane and 6 mL of tetramethyldisiloxane were added to 12 mL of cyclohexane to obtain a modified solution, 100 mL of SiO2 aged gel was added to the modified solution to obtain a modified gel solution, and the modified gel solution was placed in a water bath at a temperature of 40°C. The modified solution was replaced every 12 hours for a total of 2 times until the hydrogel floated on the liquid surface to obtain a modified SiO2 hydrogel;
[0073] (7) Drying: The modified SiO2 hydrogel was rinsed with cyclohexane and then dried in a constant temperature drying oven. The drying was carried out by step drying, first at 70°C for 6 hours and then at 130°C for 4 hours. The heating rate was set to 3°C / min. After drying, it was naturally cooled to room temperature to obtain the modified SiO2 aerogel.
[0074] Specifically, the preparation of modified asphalt includes the following steps:
[0075] S1. Mixing raw materials: After heating 1000g of 70# base asphalt to 180°C, slowly add 300g of waste tire rubber powder into the base asphalt and stir evenly to obtain asphalt rubber powder adhesive;
[0076] S2. High-speed shear mixing: Use a high-speed shearing machine to strongly shear the asphalt rubber powder adhesive at a shearing temperature of 190°C and stir continuously for 30 minutes to obtain modified asphalt.
[0077] This embodiment also provides a method for preparing heat-insulating and crack-resistant dry-mix mortar, comprising the following steps:
[0078] M1. Premixing: Mix 20 kg of expanded perlite and 15 kg of vitrified microspheres to obtain a mixed aggregate, then add 30 kg of Portland cement to the mixed aggregate, and stir preliminarily to obtain a premix;
[0079] M2, remixing: adding 12 kg of modified SiO2 aerogel and 6 kg of modified asphalt into the premix, stirring evenly to obtain a modified premix;
[0080] M3. Post-mixing: Add 0.8 kg of polypropylene fiber and 0.4 kg of starch ether into the modified premix, stir thoroughly to obtain a heat-insulating and crack-resistant dry-mix mortar.
[0081] Embodiment 4:
[0082] The present embodiment provides a heat-insulating and crack-resistant dry-mix mortar, comprising the following raw materials in parts by weight: 25 kg of silicate cement, 25 kg of expanded perlite, 20 kg of vitrified microspheres, 8 kg of modified SiO2 aerogel, 10 kg of modified asphalt, 1 kg of polypropylene fiber and 0.5 kg of a water-retaining agent; the water-retaining agent is an equal mixture of cellulose ether and starch ether.
[0083] Specifically, the preparation of modified SiO2 aerogel includes the following steps:
[0084] (1) Raw material pretreatment: The silicon-rich slag is placed in a constant temperature drying oven and dried at a temperature of 110° C. for 12 hours to obtain dry silicon-rich slag, and the dried silicon-rich slag is placed in a jaw crusher for crushing, and after crushing, it is sieved through a 200-mesh screen to obtain high-reactivity silicon-rich slag;
[0085] (2) Mixing and heating: 1000 g of highly reactive silicon-rich slag was mixed evenly with 5 L of 25 wt% sodium hydroxide solution, and then placed in a reactor for heating at a temperature of 150° C. The mixture was stirred continuously during heating and the reaction time was 10 hours to obtain a solid-liquid mixture;
[0086] (3) separation and purification: centrifuging the solid-liquid mixture at a centrifugal speed of 6000 r / min for 15 min. After the centrifugation, discarding the precipitate and collecting the supernatant to obtain a sodium silicate solution;
[0087] (4) Sol: Take 200 mL of sodium silicate solution, add 1200 mL of deionized water to dilute it, and perform ion exchange with a strong acid cation exchange resin to adjust the solution pH to 2 to obtain an ion exchange strong acid solution. Then, add ammonia water to the ion exchange strong acid solution to adjust the solution pH to 8 to obtain a SiO2 sol gel solution.
[0088] (5) Aging reaction: 100 mL of SiO2 sol-gel solution was placed on an electromagnetic heating stirrer for heating and stirring at 40°C and 100 rpm, and then allowed to stand for 24 hours to obtain SiO2 hydrogel. A 95-99% ethanol solution was added to the SiO2 hydrogel to immerse the SiO2 hydrogel, and the solution was placed in a water bath for constant temperature heating at 40°C. The ethanol solution was replaced every 8 hours, and the solution was replaced three times to obtain SiO2 aged gel.
[0089] (6) Modification reaction: 7.5 mL of dimethyldichlorosilane and 7.5 mL of tetramethyldisiloxane were added to 15 mL of cyclohexane to obtain a modified solution, 100 mL of SiO2 aged gel was added to the modified solution to obtain a modified gel solution, and the modified gel solution was placed in a water bath at a temperature of 40°C. The modified solution was replaced every 12 hours for a total of 2 times until the hydrogel floated on the liquid surface to obtain a modified SiO2 hydrogel;
[0090] (7) Drying: The modified SiO2 hydrogel was rinsed with cyclohexane and then dried in a constant temperature drying oven. The drying was carried out by step drying, first at 70°C for 4 hours and then at 130°C for 6 hours. The heating rate was set at 3°C / min. After drying, it was naturally cooled to room temperature to obtain the modified SiO2 aerogel.
[0091] Specifically, the preparation of modified asphalt includes the following steps:
[0092] S1. Mixing raw materials: After heating 1000g of 70# base asphalt to 180°C, slowly add 300g of styrene-butadiene rubber powder into the base asphalt and stir evenly to obtain asphalt rubber powder adhesive;
[0093] S2. High-speed shear mixing: Use a high-speed shearing machine to strongly shear the asphalt rubber powder adhesive at a shearing temperature of 190°C and stir continuously for 30 minutes to obtain modified asphalt.
[0094] This embodiment also provides a method for preparing heat-insulating and crack-resistant dry-mix mortar, comprising the following steps:
[0095] M1. Premixing: Mix 25 kg of expanded perlite and 20 kg of vitrified microspheres to obtain a mixed aggregate, then add 25 kg of Portland cement to the mixed aggregate, and stir preliminarily to obtain a premix;
[0096] M2, remixing: adding 15 kg of modified SiO2 aerogel and 10 kg of modified asphalt into the premix, stirring evenly to obtain a modified premix;
[0097] M3. Post-mixing: Add 1 kg of polypropylene fiber, 0.25 kg of cellulose ether and 0.25 kg of starch ether into the modified premix, stir thoroughly to obtain a heat-insulating and crack-resistant dry-mix mortar.
[0098] Comparative Example 1:
[0099] Compared with Example 4, in Comparative Example 1, no modified SiO2 aerogel is added to the thermal insulation and crack-resistant dry-mix mortar, and other conditions remain unchanged.
[0100] Comparative Example 2:
[0101] Compared with Example 4, in Comparative Example 2, no modified asphalt is added to the thermal insulation and crack-resistant dry-mix mortar, and other conditions remain unchanged.
[0102] Comparative Example 3:
[0103] Compared with Example 4, in Comparative Example 3, no water-retaining agent is added to the thermal insulation and crack-resistant dry-mix mortar, and other conditions remain unchanged.
[0104] Experimental example
[0105] The performance of the thermal insulation and crack resistant dry-mix mortars of Examples 1 to 4 of the present invention and Comparative Examples 1 to 3 was measured.
[0106] 1. According to JGJ / T70-2009 "Test method standard for basic properties of building mortar", the tensile bond strength and thermal conductivity of the mortar were measured. The test results are shown in Table 1.
[0107] Table 1
[0108]
[0109]
[0110] According to the measurement results in Table 1, the thermal insulation and crack resistance dry-mixed mortars of Examples 1 to 4 of the present invention all have high tensile bond strength and low thermal conductivity. By comparing Examples 1 to 4 with Comparative Examples 1 to 2, it can be seen that after adding modified SiO2 aerogel and modified asphalt, the tensile bond strength of the dry-mixed mortar increases and the thermal conductivity decreases, indicating that modified SiO2 aerogel and modified asphalt can significantly improve its crack resistance and thermal insulation performance.
[0111] 2. Mechanical properties determination
[0112] Refer to GB / T17671-2001 "Test Method for Strength of Silicate Cement Mortar", the specimen size is 40mm×40mm×160mm. Use a Silicate Cement Mortar Mixer to prepare the mortar, pour it into the mold twice, vibrate 60 times each time, seal the specimen and cure it in a curing box for 24 hours before demolding (curing temperature is 21℃, relative humidity>95%), use a flexural and compressive testing machine to measure the flexural strength of the specimen (loading rate 50N / s), and measure the compressive strength after the specimen is broken (loading rate 2.4KN / s), and the strength value is the average value of the test samples.
[0113] Table 2
[0114]
[0115]
[0116] According to the test results in Table 2, the heat-insulating and crack-resistant dry-mixed mortars of Examples 1 to 4 of the present invention all have high compressive strength. By comparing Examples 1 to 4 with Comparative Examples 1 to 2, it can be seen that after adding modified SiO2 aerogel and modified asphalt, the compressive strength of the dry-mixed mortar increases, indicating that modified SiO2 aerogel and modified asphalt can significantly improve its compressive performance.
[0117] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
[0118] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. Heat-insulating and crack-resistant dry-mix mortar, characterized in that: The invention comprises the following raw materials in parts by weight: 25-40 parts of silicate cement, 15-25 parts of expanded perlite, 10-20 parts of vitrified microspheres, 2-10 parts of modified asphalt, 1-8 parts of modified SiO2 aerogel, 0.5-1 parts of polypropylene fiber and 0.2-0.5 parts of water retaining agent; the modified SiO2 aerogel is prepared from silicon-rich slag as raw material by raw material pretreatment, mixing heating, separation and purification, sol, aging reaction, modification reaction and drying; the modified asphalt is prepared from base asphalt and rubber powder as raw materials by raw material mixing and high-speed shear mixing.
2. The heat-insulating and crack-resistant dry-mix mortar according to claim 1, characterized in that: The water retaining agent is one or both of cellulose ether and starch ether.
3. The heat-insulating and crack-resistant dry-mix mortar according to claim 1, characterized in that: The preparation method of modified SiO2 aerogel comprises the following steps: (1) Raw material pretreatment: The silicon-rich slag is placed in a constant temperature drying oven for drying to obtain dry silicon-rich slag, and the dry silicon-rich slag is placed in a jaw crusher for crushing. After crushing, the dried silicon-rich slag is sieved to obtain high-reactivity silicon-rich slag; (2) Mixing and heating: Highly reactive silicon-rich slag and sodium hydroxide solution are mixed evenly, and then placed in a reactor for heating. Stirring is continued during the heating period. After the heating is completed, a solid-liquid mixture is obtained; (3) Separation and purification: centrifuging the solid-liquid mixture, discarding the precipitate after centrifugation, and collecting the supernatant to obtain a sodium silicate solution; (4) Sol: Add deionized water to the sodium silicate solution to dilute it, and perform ion exchange through a strong acid cation exchange resin to obtain an ion exchange strong acid solution, and then add ammonia water to the ion exchange strong acid solution to adjust the pH of the solution to obtain a SiO2 sol-gel solution; (5) Aging reaction: The SiO2 sol-gel solution is placed on an electromagnetic heating stirrer for heating and stirring, and then allowed to stand to obtain a SiO2 hydrogel. An ethanol solution is added to the SiO2 hydrogel to immerse the SiO2 hydrogel, and the solution is placed in a water bath for constant temperature heating. The ethanol solution is replaced to obtain a SiO2 aged gel. (6) Modification reaction: adding a modifier to cyclohexane to obtain a modified solution, adding the modified solution to the aged SiO2 gel to obtain a modified gel solution, placing the modified gel solution in a water bath, and replacing the modified solution until the hydrogel floats on the liquid surface to obtain a modified SiO2 hydrogel; (7) Drying: The modified SiO2 hydrogel is rinsed with cyclohexane and then dried in a constant temperature drying oven. After drying, it is naturally cooled to room temperature to obtain a modified SiO2 aerogel.
4. The heat-insulating and crack-resistant dry-mix mortar according to claim 3, characterized in that: In step (1), the temperature of the constant temperature drying oven is 100-110° C., the drying time is 12-16 hours, the feed particle size of the jaw crusher is 480-1040 mm, and the mesh size of the sieve is 100-200 meshes; in step (2), the highly reactive silicon-rich slag is added to the sodium hydroxide solution, the liquid-to-solid ratio is 2-5:1, the concentration of the sodium hydroxide solution is 10-25wt%, the reaction temperature is 90-150° C., and the reaction time is 1-10 hours.
5. The heat-insulating and crack-resistant dry-mix mortar according to claim 3, characterized in that: In step (3), the centrifugal speed is 4000-6000 r / min, and the centrifugal time is 10-15 min. In step (4), the volume ratio of the sodium silicate solution to deionized water is 1:3-6, the solution pH is adjusted to 2 after the strong acid cation exchange resin, and ammonia water is added to adjust the solution pH to 7-9.
6. The heat-insulating and crack-resistant dry-mix mortar according to claim 3, characterized in that: In step (5), the temperature of the electromagnetic heating stirrer is set to 40°C, the speed is set to 30-100 rpm, and the mixture is left to stand for 6-48 hours. The concentration of the ethanol solution is 95-99 vt%, the temperature of the water bath is 40°C, and the ethanol solution is replaced every 8 hours for 3 times.
7. The heat-insulating and crack-resistant dry-mix mortar according to claim 3, characterized in that: In step (6), the modifier is a mixture of dimethyldichlorosilane and tetramethyldisiloxane, wherein dimethyldichlorosilane and tetramethyldisiloxane are mixed in equal amounts, the volume ratio of cyclohexane to the modifier is 1:1, the modified solution accounts for 10-30% of the volume of the SiO2 aged gel, the temperature of the water bath is 40°C, the modified solution is replaced every 12 hours, for a total of 2 changes, the duration is 24 hours; in step (7), the drying is performed by step drying, first drying at 60-70°C for 4-6 hours, and then drying at 120-130°C for 4-6 hours, and the heating rate is set to 3°C / min.
8. The heat-insulating and crack-resistant dry-mix mortar according to claim 1, characterized in that: The preparation method of modified asphalt comprises the following steps: S1. Mixing raw materials: After heating the base asphalt, slowly add the rubber powder into the base asphalt and stir evenly to obtain asphalt rubber powder adhesive; S2. High-speed shear mixing: Use a high-speed shearing machine to strongly shear the asphalt rubber powder adhesive and continuously stir it to obtain modified asphalt.
9. The heat-insulating and crack-resistant dry-mix mortar according to claim 8, characterized in that: The base asphalt in S1 is 70# base asphalt, the heating temperature is 170-180°C, the rubber powder is one or two of styrene-butadiene rubber powder and waste tire rubber powder, and the rubber powder accounts for 10-30% of the asphalt mass; the shear temperature in S2 is 180-190°C, and the stirring time is 20-30min.
10. A method for preparing heat-insulating and crack-resistant dry-mix mortar, characterized in that: The steps include: M1. Premixing: Mix expanded perlite and vitrified microspheres to obtain mixed aggregate, then add silicate cement to the mixed aggregate, preliminarily stir evenly to obtain a premix; M2. Remixing: adding the modified SiO2 aerogel and the modified asphalt into the premix, stirring evenly to obtain a modified premix; M3. Post-mixing: Add polypropylene fiber and water-retaining agent into the modified premix, stir thoroughly to obtain heat-insulating and crack-resistant dry-mix mortar.